2017
DOI: 10.3174/ajnr.a5455
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Spaces in Old Age: Assessment, Distribution, and Correlation with White Matter Hyperintensities

Abstract: BACKGROUND AND PURPOSE:The visual rating scales for perivascular spaces vary considerably. We sought to develop a new scale for visual assessment of perivascular spaces and to further describe their distribution and association with white matter hyperintensities in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 31 publications
8
47
0
Order By: Relevance
“…We used a visual rating scale to evaluate PVS, as fully reported elsewhere. 18 Briefly, we used T1 and T2 images to assess PVS in different brain areas (e.g., frontal lobe, parieto-occipital lobe, basal ganglia, thalami, and cerebellum) in each brain hemisphere. In each region, the number of visible PVS was measured on a 0–3 point scale: 0, no visible PVS; 1, 1–5 PVS; 2, 6–10 PVS; or 3, >10 PVS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a visual rating scale to evaluate PVS, as fully reported elsewhere. 18 Briefly, we used T1 and T2 images to assess PVS in different brain areas (e.g., frontal lobe, parieto-occipital lobe, basal ganglia, thalami, and cerebellum) in each brain hemisphere. In each region, the number of visible PVS was measured on a 0–3 point scale: 0, no visible PVS; 1, 1–5 PVS; 2, 6–10 PVS; or 3, >10 PVS.…”
Section: Methodsmentioning
confidence: 99%
“…The visual rating scale for PVS had the weighted κ statistic of 0.77 for both intrarater and inter-rater reliability. 18 …”
Section: Methodsmentioning
confidence: 99%
“…Imaging the perivascular spaces (PVS), also known as Virchow-Robin space, has significant clinical value. Many recent studies have shown pathological alteration of PVS in a range of neurological disorders (Bacyinski et al, 2017;Banerjee et al, 2017;Brown et al, 2018;Cavallari et al, 2018;Feldman et al, 2018;Kalaria, 2018;Krueger and Bechmann, 2010;Laveskog et al, 2018;Park et al, 2017). It is also believed that PVS plays a major role in the clearance system, accommodating the influx of CSF to brain parenchyma through peri-arterial space, and the efflux of interstitial fluid to the lymphatic system through peri-venous space (Rasmussen et al, 2018;Tarasoff-Conway et al, 2015;Bacyinski et al, 2017;Iliff et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis may also increase the relative size of the PVS due WM atrophy 23 , and PVS size is also known to increase with age 24 . Moreover, CBF and CBV were generally found to be reduced in the normal appearing white matter in MS 25 .…”
Section: Discussionmentioning
confidence: 99%